Transverse maxillary and mandibular growth during and after Bionator therapy: study with metallic implants - Monini, André Da Costa [UNESP]; Gandini Júnior, Luiz Gonzaga [UNESP]; Maia, Luiz Guilherme Martins [UNESP]; Santos-pinto, Ary Dos [UNESP] (Dental Press International, 2013)
INTRODUCTION: This study evaluated posteroanterior cephalograms before and after treatment and long term follow-up of Class II division 1 patients treated with bionator. OBJECTIVE: The objective was to demonstrate the transverse growth of maxilla and mandible during and after bionator therapy. METHODS: Measurement of transverse dimensions between posterior maxillary and mandibular implants, as well as the distances between the buccal, gonial and antegonial points were recorded. Measurements were analyzed at three periods: T1 = before bionator therapy, T2 = after bionator therapy and T3 = 5.74 years after T2. RESULTS: There was statistically significant transverse increase due to growth and/or treatment for all variables, except for the distance between the anterior maxillary implants. CONCLUSIONS: During the study period only the anterior maxillary area did not show transverse growth.

INTRODUÇÃO: esse estudo envolve a avaliação de telerradiografias posteroanteriores pré- e pós-tratamento com Bionator, bem como, em longo prazo, de pacientes Classe II divisão 1. OBJETIVO: o objetivo desse trabalho é demonstrar o crescimento transversal da maxila e mandíbula durante e após o uso do Bionator. MÉTODOS: as mensurações das distâncias transversais entre os implantes posteriores da maxila e mandíbula, bem como as das distâncias entre os pontos jugal, gônio e antigônio, foram tomadas em três tempos: T1, antes da terapia com Bionator; T2, após a terapia como Bionator; e T3, 5,74 anos após T2. RESULTADOS: ocorreu aumento transversal estatisticamente significativo por crescimento e/ou por tratamento em todas as variáveis estudadas, com exceção da distância entre os implantes anteriores da maxila. CONCLUSÕES: durante o período do estudo, somente a região anterior da maxila não apresentou crescimento transversal.
Crescimento transversal dos maxilares durante e após a terapia com Bionator: estudo com implantes metálicos
Keywords: Aparelhos ativadores; Má oclusão de Angle Classe II; Desenvolvimento maxilofacial; Activator appliances; Angle Class II malocclusion; Maxillofacial development